Assessment of the effectiveness of channels of distribution models in the sales performance of an organization: The case of Coca-Cola Morogoro region. - Emmanuel, Laswai M. (Mzumbe University, 2024)
A dissertation submitted to school of business in partial fulfilment of the requirement for award of Master degree of business administration Mzumbe University 2013